2003
DOI: 10.1073/pnas.1832982100
|View full text |Cite
|
Sign up to set email alerts
|

A tenth atp gene and the conserved atpI gene of a Bacillus atp operon have a role in Mg 2+ uptake

Abstract: The atp operon of alkaliphilic Bacillus pseudofirmus OF4, as in most prokaryotes, contains the eight structural genes for the F-ATPase (ATP synthase), which are preceded by an atpI gene that encodes a membrane protein of unknown function. A tenth gene, atpZ, has been found in this operon, which is upstream of and overlapping with atpI. Most Bacillus species, and some other bacteria, possess atpZ homologues. AtpZ is predicted to be a membrane protein with a hairpin topology, and was detected by Western analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…We found a weak expression of the atpI gene in comparison with that of the atpB gene, as occurs in E. coli and Ilyobacter tartaticus (Schneppe et al, 1991;Meier et al, 2003). Poor or null atpI gene expression is a common feature among bacteria (Amaresh & Ljungdahl, 1997;Walker et al, 1984;Hicks et al, 2003). (Frasch, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We found a weak expression of the atpI gene in comparison with that of the atpB gene, as occurs in E. coli and Ilyobacter tartaticus (Schneppe et al, 1991;Meier et al, 2003). Poor or null atpI gene expression is a common feature among bacteria (Amaresh & Ljungdahl, 1997;Walker et al, 1984;Hicks et al, 2003). (Frasch, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…When atpI, originally called uncI, was first reported (10), it was suggested that it encoded a pilot protein with a role in assembly of the membrane sector of the synthase, although AtpI clearly did not have an essential role, since deletion of the atpI gene from Escherichia coli only slightly reduced the growth yield and ATPase activity (11). Similarly, we recently showed that atpI, as well as the atpZ gene that is found upstream of atpI in many low %GC bacteria, could be deleted from the chromosome of alkaliphilic Bacillus pseudofirmus OF4 without apparent loss of the capacity to grow nonfermentatively (8,12).…”
mentioning
confidence: 83%
“…Table 1 lists the bacterial strains and plasmids used. The WT (wild-type) strain is alkaliphilic Bacillus pseudofirmus OF4 811M (12). The ⌬atpZ, ⌬atpI, ⌬atpZI, and ⌬F o strains are from laboratory stocks (12,31).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations